Preventive anti-inflammatory activity of an aqueous extract of larrea divaricata cav. and digestive and hematological toxicity - Davicino, Roberto Carlos (2015)
Larrea divaricata Cav. commonly known as “jarilla hembra” is used in folklore medicine as anti-inflammatory. There was no scientific evidence justifying the medicinal use of the aqueous extract for inflammation diseases. Nowadays, there are two principal types of anti-inflammatory drugs: Steroidal anti-inflammatory drugs (corticosteroids) and non-steroidal anti-inflammatory drugs (NSAIDs), which exert gastrointestinal ulceration and bleeding. In this work the preventive anti-inflammatory activity of L. divaricata aqueous extract (AE) in C3H/He mice was determined by carrageenan- induced inflammation and ear edema tests, also its toxicity on gastric tissues and on blood cells was studied. The chromatographic profile showed: nordihydroguaiaretic acid (NDGA) as majority compound. AE exerted anti-inflammatory action without inducing gastric or blood cell toxicities. Also, it could modulate anti-inflammatory and pro-inflammatory cytokines. NDGA was not the compound responsible of the anti-inflammatory action. This work rescues the potentiality of AE as a gastric and blood cells innocuous anti-inflammatory agent and confirms its ethno- pharmacological uses.